The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.ijcard.2014.12.046
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of absolute risk reduction of cardiovascular events with perindopril for individual patients with stable coronary artery disease — Results from EUROPA

Abstract: ISRCTN37166280.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…34,35 These papers join a growing list of papers showing clinically important variation in benefits when trial results are risk stratified, typically showing that an identifiable subgroup of higher-risk patients often account for most of the treatment benefit. [36][37][38][39][40][41][42][43][44][45][46] Another consistent finding was that the median predicted outcome risk in these trials was lower than the mean predicted risk (i.e. MMRR < 1).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…34,35 These papers join a growing list of papers showing clinically important variation in benefits when trial results are risk stratified, typically showing that an identifiable subgroup of higher-risk patients often account for most of the treatment benefit. [36][37][38][39][40][41][42][43][44][45][46] Another consistent finding was that the median predicted outcome risk in these trials was lower than the mean predicted risk (i.e. MMRR < 1).…”
Section: Discussionmentioning
confidence: 86%
“…Whereas several trials in our database of trials exhibited large heterogeneity in predicted outcome risk, overall the results of our analyses were somewhat less extreme than previous published examples might have suggested. [36][37][38][39][40][41][42][43][44][45] There are several explanations for this observation. First, risk heterogeneity may be somewhat restricted in large phase III randomized studies if they tend to enroll homogeneous patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Although these data show a benefit from the use of ACE inhibitors in the treatment of heart disease, the residual risk of events (1.0 minus RR) documented in these studies is close to or greater than 70%. Additional studies from well-conducted clinical trials shows that the "residual risk" for cardiovascular events is substan-tially greater than the risk reduction achieved by these agents (1,12,18,36,60,75,132,133,(145)(146)(147).…”
Section: H409mentioning
confidence: 99%
“…37 For preventive therapies that are associated with considerably higher NNTs, such as blood-pressure-lowering therapy (5-year NNTs between 80 and 160, 37 corresponding with 10-year NNTs between 40 and 80), previous studies have shown that applying a prediction model may similarly result in higher net benefit compared with a strategy in which all patients are treated. 38,39 Importantly, in patients at relatively high risk of cardiovascular events, the net benefit of a prediction-based treatment strategy will be comparable to a strategy in which all patients are treated because high-risk patients are likely to exceed the treatment threshold and therefore all will be treated in both scenarios. Therefore, the additional value of a predictionbased strategy lies in selective treatment of patients in the lower risk groups (not exceeding the treatment threshold).…”
Section: Discussionmentioning
confidence: 99%